Cobalt and / or cerium doped zeolites for bifunctional catalytic hydroisomerization.
Patent Information
- Application Number
- JP2023577526
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-17
- Filing Date
- 2022-06-08
- Publication Date
- 2025-04-15
AI Technical Summary
Zeolite-based catalysts for hydroisomerization of light paraffins suffer from cracking side reactions, and metal oxide catalysts are prone to deactivation by catalyst poisons such as S, N, H2O, and Cl.
Development of heteroatom-doped beta zeolites containing cerium and/or cobalt as extra-framework species, with Group VIII or VIB metals, which are synthesized before crystallization and calcined under specific conditions to enhance isomerization performance.
The catalysts exhibit improved selectivity and activity for hydroisomerization, reducing cracking and maintaining high conversion rates of light paraffins, even at elevated temperatures.
Smart Images

Figure 00000020_0000 
Figure 00000020_0001 
Figure 00000021_0000
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to and the benefit of U.S. Application No. 17 / 349989, filed June 17, 2021, which is incorporated by reference in its entirety.
[0002] The present disclosure relates to the hydroisomerization of light paraffins, and more particularly to novel catalysts for the hydroisomerization of light paraffins. [Background technology]
[0003] The hydroisomerization of light normal paraffins is the primary reaction for utilizing certain petroleum resources to increase the octane number of gasoline fuels. Zeolite catalysts have been used for this purpose. However, zeolite-based light paraffin hydroisomerization catalysts can suffer from a side reaction called cracking. Metal oxide catalysts have been developed for use in these reactions because they have high activity and selectivity for the hydroisomerization of light normal paraffins. However, the S, N, and H 2 The presence of catalyst poisons such as O and Cl can reduce the activity of the catalyst. Summary of the Invention
[0004] Provided herein is a process for hydroisomerization of a hydrocarbon feedstock comprising contacting the hydrocarbon feedstock with hydrogen and a catalyst to obtain a hydrocarbon product having an increase in branched hydrocarbons compared to the hydrocarbon feedstock. The catalyst of the invention comprises a heteroatom-doped beta zeolite comprising extra-framework species comprising trivalent cations, cerium and / or cobalt as framework metal oxides, and 0.01-1.5 wt.% of a Group VIII or Group VIB metal, or combinations thereof.
[0005] Also provided herein is a method for the synthesis of heteroatom-doped beta zeolite containing cerium or cobalt as an extra-framework species. The method comprises the steps of: 2 and a framework metal oxide (i.e., a reaction mixture suitable for the synthesis of beta zeolite, particularly aluminum-containing beta zeolite) in the presence of a cerium source and / or a cobalt source. 2 the molar ratio of structure directing agent cation Q to SiO to framework metal oxide of the reaction mixture greater than 10; 2 The molar ratio of SiO in the reaction mixture is greater than 0. 2 the molar ratio of water to SiO in the reaction mixture being 0 to 1; 2 and a molar ratio of the alkali metal M to the Al source in said reaction mixture that is greater than 5. 2 The molar ratio of cerium and / or cobalt is added to the reaction mixture before crystallization occurs, for example in the form of cerium and / or cobalt salts. The method of the present invention for synthesizing heteroatom-doped beta zeolite includes calcining the heteroatom-doped beta zeolite under inert, oxidative and / or steam conditions at a temperature between 100° C. and 800° C. such that framework heteroatoms are converted to extraframework species. The reaction mixture can further include a mineralizer and / or a structure directing agent.
[0006] These and other features and attributes of the disclosed methods and compositions of the present disclosure, as well as their advantageous applications and / or uses, will become apparent from the following detailed description. [Brief description of the drawings]
[0007] To assist those of ordinary skill in the relevant art in making and using the subject matter herein, reference is made to the accompanying drawings, in which:
[0008] [Figure 1] FIG. 1 is a graph of the X-ray diffraction of Ce-doped Al-Beta zeolite (top line) versus Al-Beta zeolite (bottom line).
[0009] [Diagram 2] Figure 2 shows a graph of the DRUV-vis results of Ce-doped Al-Beta zeolite before and after calcination, referenced to CeO2 (the signal has been scaled down by a factor of 20 for visual clarity).
[0010] [Diagram 3] FIG. 3 shows the isomerization selectivity (%) versus n-heptane conversion (%) for heteroatom-doped zeolites at 230° C. and WHSV of 2, 4, and 6 / h.
[0011] [Figure 4] FIG. 4 shows the isomerization selectivity (%) versus n-heptane conversion (%) for heteroatom-doped zeolites at 250° C. and WHSV of 2, 4, 6 / hr or 4, 6 / hr.
[0012] [Figure 5A] Figure 5A shows the increase in RON versus light gas (C1–C4) wt.% production per hour at 250 °C and LHSVs of 3 and 6 for the catalyst Pt / Fe / WZrOx operated at 170 °C.
[0013] [Figure 5B] FIG. 5B is a graph showing n-C7 conversion to light gas production by cracking.
[0014] [Figure 6] Figure 6 shows the relative conversion of n-C6, n-C7 at 250°C and LHSV of 3.6 per hour for the four catalysts described in Example 3. The results are for catalyst Pt / Fe / WZrOx operated at 170°C.
[0015] [Figure 7] FIG. 7 shows the isomer selectivity versus conversion at 230° C. with WHSV of 0.75, 1, and 1.5 h−1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] As used in this disclosure and claims, the singular forms "a," "an," and "the" include the plural forms unless the specification indicates otherwise.
[0017] The term "and / or" as used herein in expressions such as "A and / or B" is intended to include "A and B," "A or B," or "A" and "B."
[0018] "C n The term "hydrocarbon" refers to a hydrocarbon compound containing carbon atoms having n total carbon atoms in its molecular structure, or a mixture of two or more such hydrocarbon compounds. Varying degrees of unsaturation may be present in such hydrocarbons.
[0019] The terms "paraffin", "alkane" and "saturated hydrocarbon" are used interchangeably herein and include those having a C n H 2n+2 It refers to a hydrocarbon having the formula:
[0020] As used herein, the terms "straight chain" and "normal" are used interchangeably and refer to a hydrocarbon with no side chain branching.
[0021] "Cracking" is the conversion of a hydrocarbon molecule into two smaller hydrocarbon molecules.
[0022] The terms "isomerization" and "hydroisomerization" refer to the skeletal rearrangement of hydrocarbons, in particular the conversion of normal paraffins to branched paraffins.
[0023] The term "weight hourly space velocity" (WHSV) refers to a measure of the weight of feed mixture flowing per unit weight of catalyst per hour.
[0024] "Liquid hourly space velocity" (LHSV) is a measure of the volume of feed mixture flowing per unit volume of catalyst per hour.
[0025] "Variable oxidation state metal" refers to a metal that has two or more accessible oxidation states other than the zero oxidation state.
[0026] The term "total surface area" means the total specific external and internal surface area of a dispersed or porous solid (microporous material), as defined in ISO 9277, and is the total specific surface area of the adsorbed N 2 It is obtained by measuring the amount of adsorption / desorption isotherm.
[0027] Unless otherwise specified, ambient temperature (also referred to as "room temperature") is about 25°C.
[0028] Provided herein is a process for hydroisomerizing a hydrocarbon feedstock, comprising contacting the hydrocarbon feedstock with hydrogen and a catalyst to obtain a hydrocarbon product having an increase in branched hydrocarbons relative to the hydrocarbon feedstock. The catalyst comprises a heteroatom-doped zeolite beta, particularly a cerium and / or cobalt-doped beta zeolite, 0.01 to 1.5 wt. % Group VIII or Group VIB metal, or a combination thereof, and may further comprise a metal oxide binder. In the process of the invention, the heteroatom-doped beta zeolite comprises a trivalent cation as a framework metal oxide and an extraframework species comprising cerium and / or cobalt. The heteroatom-doped beta zeolite of the invention has a SiO ratio of greater than 10 to the framework / extraframework oxide. 2 In one embodiment, the heteroatom-doped beta zeolite of the present invention may further comprise a molar ratio of Al greater than 8, in particular greater than 10, such as greater than 10 and 2000 or 1000, for example from 20 to 200, or from 30 or 40 to 100 or 150. 2 O 3 SiO 2In certain embodiments, the heteroatom-doped beta zeolite of the present invention comprises a molar ratio of cerium and / or cobalt metal oxide (CeO) that is greater than 10, e.g., greater than 10 and 2000 or greater than 15 and 1000, e.g., greater than 30 or 40 or greater than 50 and 500 or 300. x or CoO x (morphology of SiO 2 In an embodiment, the heteroatom-doped beta zeolite of the present invention comprises a Group VIII or Group VIB metal and / or is selective for the conversion of n-heptane. Thus, in an embodiment, the present invention relates to the use of a cerium and / or cobalt doped beta zeolite having a trivalent cation (e.g., Al) as a framework metal oxide, and an extraframework species comprising cerium and / or cobalt, in a hydroisomerization catalyst, e.g., a hydroisomerization catalyst, in a process for hydroisomerization of a hydrocarbon feed comprising contacting the hydrocarbon feed with hydrogen and the catalyst to obtain a hydrocarbon product having an increase in branched hydrocarbons relative to the hydrocarbon feed, the catalyst comprising a cerium and / or cobalt doped beta zeolite, 0.01 to 1.5 wt % of a Group VIII and / or Group VIB metal, particularly Pt, and optionally a metal oxide binder.
[0029] In the hydroisomerization process of the present invention, the hydrocarbon feedstock is subjected to a hydroisomerization reaction at an operating temperature of 100° C. to 450° C., an operating pressure of 0 psig to 1000 psig, and a hydrothermal reaction of 0.1 hr. -1 From 10 hours -1 and a hydrogen / hydrocarbon molar ratio of from 0 to 100. In an embodiment, the catalyst comprises 0.1 wt% to 1.5 wt% Pt. The hydrocarbon feedstock comprises any of the following hydrocarbons: n-pentane, n-hexane, n-heptane, and combinations thereof.
[0030] As described herein, the method of the present invention for synthesizing heteroatom-doped beta zeolite containing cerium or cobalt as an extra-framework species comprises the steps of: 2and a skeletal metal oxide (particularly a trivalent skeletal metal oxide, e.g., Al). Optionally, the reaction mixture includes a structure directing agent and / or a mineralizer. The reaction mixture is crystallized by adding 0 to 4% of the SiO 2 of the reaction mixture. 2 The molar ratio of structure directing cation Q to SiO to framework metal oxide in the reaction mixture is greater than 10. 2 Molar ratio of SiO in the reaction mixture greater than 0 2 Molar ratio of water to SiO in the reaction mixture is 0-1. 2 and the molar ratio of the alkali metal M to the Al source in the reaction mixture is greater than 5, e.g., greater than 10. 2 The method of the present invention for synthesizing heteroatom-doped beta zeolite includes calcining the heteroatom-doped beta zeolite under inert, oxidative and / or steam conditions at a temperature between 100°C and 800°C such that the framework heteroatoms are converted to extra-framework species. Beta zeolite is characterized by a molar ratio of SiO to framework metal oxide. 2 The molar ratio of SiO to SiO is greater than 10. Beta zeolite is also known as 2 Against Al 2 O 3 The molar ratio of is about 8 or more, in particular 10 or more, for example 10 to 2000 or less, or 1000 or less, for example 20 to 200 or 30 or 40 to 100 or 150 or less. Beta zeolite is SiO 2 , cerium and / or cobalt metal oxide (CeO x or CoO x ) is 10 or more, for example 10 or more and 2000 or less, or 15 or more and 1000 or less, for example 30 or 40 or 50 or more and 500 or 300 or less.
[0031] To produce the heteroatom-doped zeolites of the present invention, heteroatoms are introduced into the synthesis gel prior to crystallization. By utilizing the method of the present invention, heteroatoms can be present as framework sites and extra-framework species. According to the UV-vis measurements of DR, many of the extra-framework species found as impurities in heteroatom-containing zeolites have a distinct dispersion compared to that of the bulk. Thus, such species can be used as promoters in close proximity to the acid sites of the zeolite framework to enhance the performance of bifunctional reactions. This differs from zeolite beta and other zeolites of the prior art, where heteroatoms are introduced into framework sites after synthesis. Verification of the incorporation of heteroatoms into the framework T sites of zeolites is limited due to available characterization techniques. Although indirect incorporation has been reported, such as through catalytic test results, it was previously unclear whether incorporation is via framework sites or extra-framework species.
[0032] In bifunctional heptane hydroisomerization, various heteroatoms are beneficial as promoters. Such a promoting effect has been confirmed when heteroatoms are present in framework sites or ion exchange sites. For example, the addition of zinc, titanium, and zirconium to framework sites to improve activity and selectivity of ZSM-48 crystals has been described in US Patent Application Publication No. 2015 / 0273450 A1. The maximum yield for isohexadecane was obtained and confirmed when the material contained titanium. In the case of framework introduction as described, activity improvement for hydroisomerization included Mn, Fe, and Ga. The introduction of different heteroatoms in ion exchange sites is beneficial for activity and selectivity. Examples include La, Fe, and Co, and are described in the following literature: Liu et al., Rare Earth Metals Ion-exchanged β-zeolites as Supports of Platinum Catalysts for Hydroisomerization of n-heptane, Chin. J. Chem. Eng., 19, 278, 2011; Ushiki et al., Co-loading of Pt and Fe*BEA Zeolite for Enhanced Isomerization Selectivity in n-Heptane Conversion, Chem Lett. 47, 1428-1430, 2018; and Izutsu et al., Synthesis and Characterization of Chromium-Added Pt / Beta Zeolite and its Catalytic Performance of n-Heptane Isomerization, Catal. Lett., 143, 486, 2013.
[0033] As described in the Examples herein, the catalyst of the present invention is selective and highly active for light linear paraffins compared to the conventional monometallic catalyst of Pt / Al-Beta catalyst. 5 , C 6 , and C 7 Selective for mixed hydrocarbon feed. Pt / Fe / WZrO xCompared to the mixed metal oxide catalysts of the catalyst and Pt / Al-MOR catalyst, the present catalyst offers comparable or better conversion and selectivity while operating at higher temperatures.
[0034] As further taught by the examples, non-conventional heteroatoms such as cerium ("Ce") and cobalt ("Co") are added to beta zeolite synthesis to obtain heteroatom-doped zeolite Al-beta zeolite. Thus, in one aspect, the present invention relates to a method for synthesizing heteroatom-doped beta zeolite having a trivalent cation (e.g., Al) as a framework metal and an exo-framework species including Ce and / or Co, the method comprising preparing Al-beta zeolite by conventional methods, except that the heteroatoms (i.e., Ce and / or Co) are introduced into the reaction mixture (or synthesis gel) before crystallization occurs. Thus, the method comprises the step of preparing a reaction mixture (or synthesis gel) having a composition suitable for preparing Al-beta zeolite, the reaction mixture (or synthesis gel) further comprising at least one source of cerium and / or cobalt. Suitable sources of cerium and cobalt include their salts, particularly their water-soluble salts, such as nitrates, sulfates, acetates, and halides, such as chlorides and bromides, of cerium and / or cobalt. In one embodiment, at least one source of cerium and / or cobalt (CeO x or CoO x (expressed as 2 is greater than 10, e.g., greater than 10 to 2000 or greater than 15 to 1000, e.g., greater than 30 or 40 or greater than 50 to 500 or to 300. The reaction mixture is then heated until crystallization occurs. The crystallized product from the hot reaction mixture can be conventionally separated, washed with water and dried. The method may also further comprise calcining the heteroatom-doped (Ce- and / or Co-doped) beta zeolite at a temperature of 100° C. to 800° C. under inert, oxidative and / or steam conditions to convert at least a portion of the Ce and / or Co atoms to extra-framework species.
[0035] When applied to hydroisomerization reactions, these zeolites exhibited conversion selectivity trade-off patterns comparable to those of conventional monometallic zeolites, such as Pt / Al-beta zeolites. Certain elements, such as tin ("Sn"), did not exhibit such improvements, demonstrating the importance of element selection. Pt / Fe / WZrO x In the hydroisomerization reaction of the mixed hydrocarbon feed, Pt / Ce,Al-Beta was used at higher temperatures (Pt / Ce,Al-Beta 250°C, Pt / Fe / WZrO x 170℃) 5 , C 6 , and C 7 The progress in conversion-selectivity trade-off was confirmed and compared with conventional Pt / Al-beta prepared in a similar manner.
[0036] As mentioned above, heteroatoms are introduced in the synthesis before the crystallization of the zeolite and can be partially removed from the framework sites during calcination. This methodology is in contrast to heteroatom-containing zeolites that have heteroatoms in the framework sites. DRUV-vis measurements show that extra-framework species can be found as impurities in heteroatom-doped zeolites, dispersing differently from the bulk oxides and impurities in heteroatom-containing zeolites. Such extra-framework species are useful as promoters that are located in close proximity to the acid sites of the zeolite framework, improving the performance of bifunctional reactions and the properties of the catalysts used therein.
[0037] Beta Zeolite As described in U.S. Pat. No. 3,308,069 and U.S. Reissue Pat. No. 28,341, beta zeolite (sometimes called "zeolite beta") is a zeolite consisting of SiO 2 bridged by shared oxygen atoms. 4 and AlO 4It is a crystalline aluminosilicate zeolite with an open three-dimensional framework of tetrahedra in which the ratio of oxygen atoms to the sum of aluminum and silicon atoms is equal to 2. The negative charge of the aluminum-containing tetrahedra is balanced by the inclusion of cations, such as alkali metal ions and alkaline earth metal ions, within the crystal.
[0038] Zeolites have a crystalline structure with molecular-sized channels. The interstices are originally occupied by water of hydration. After at least partial dehydration, these zeolites become efficient adsorbents, and adsorbed molecules are held within the interstices. The interstitial dimensions of the openings in the crystal lattice restrict the size and shape of the molecules that can be adsorbed. Thus, separation of mixtures of different molecules based on molecular dimensions is possible, with certain molecules being adsorbed by the zeolite and others being excluded from adsorption.
[0039] According to an embodiment of the present invention, the beta zeolite can have a composition calculated as follows: [XNa(1.0±0.1X)TEA]AlO 2 .YSiO 2 .WH 2 O where X is less than 1 or less than 0.75, TEA represents tetraethylammonium ion, Y is greater than 5 and less than 100, and W is up to about 4 depending on the dehydration conditions and the metal cations present. The TEA content is calculated by the difference between the analytical value for sodium and the ultimate theoretical cation ratio for Al of 1.0 / 1.
[0040] Beta zeolite is a mixture of oxides, or zeolite with the chemical composition Na, from a reaction mixture containing tetraethylammonium hydroxide. 2 O, Al 2 O 3 , [(C 2 H 5 ) 4 N] 2 O, SiO 2 and H 2The material, which can be described as a mixture of oxides such as SiO, is prepared by heating in aqueous solution at temperatures between about 75°C and 200°C until crystallization occurs. The composition of the reaction mixture, expressed as molar ratios, falls within the following ranges: SiO 2 / AlO 2 About 10 to about 200; Na 2 O / tetraethylammonium hydroxide (TEAOH) from about 0.0 to about 0.1; TEAOH / SiO 2 about 0.1 to about 1.0; and H 2 O / TEAOH from about 20 to about 75. The product which crystallizes from the hot reaction mixture is separated by centrifugation or filtration, washed with water, and dried. The material thus obtained can be calcined by heating in air or an inert atmosphere at temperatures ranging from about 400°F (204°C) to about 1700°F (927°C) or higher, so long as the temperature is not sufficient to destroy the crystallinity.
[0041] The preparation of beta zeolite involves reacting an amorphous silica solid or sol with a soluble aluminate in an aqueous medium along with an aqueous solution of tetraethylammonium hydroxide. The aluminate may be sodium aluminate or tetraethylammonium aluminate. Amorphous silica-alumina solids may also be used as the source of silica and alumina. The reaction mixture is initially stirred continuously or periodically to ensure homogeneity. After this stirring, stirring may be discontinued. It is not necessary to stir the reaction mass during the formation and crystallization of the zeolite, but stirring at such later stages has not been found to be detrimental.
[0042] The crystallization procedure can be carried out at a temperature within the range of about 75° C. to about 200° C. The pressure during crystallization is atmospheric pressure or at least a pressure corresponding to the vapor pressure of water in equilibrium with the reactant mixture. Heating is continued until the desired crystalline zeolite product is formed. The zeolite crystals are then separated from the mother liquor and washed, such as with distilled water.
[0043] Beta zeolites differ from other crystalline aluminosilicates in several ways. First, they have a new structure defined by X-ray crystallography. Second, beta zeolites have a new combination of adsorption properties: they are highly selective for cyclohexane, n-hexane, and H 2 The adsorption capacities for O are almost equal or of the same order. 2 The O adsorption capacity does not exceed that of cyclohexane. 2 / AlO 2 The ratio is variable, ranging from 10 to 100 or even as high as 150.
[0044] Beta zeolite catalysts can be prepared by calcining the original sodium form of beta zeolite and / or by replacing a major portion of the sodium in the zeolite with other metal ions and / or ammonium ions. If calcination is performed prior to ion exchange, some or all of the resulting hydrogen ions can be replaced with metal ions in the ion exchange step.
[0045] Beta zeolite is also useful as an adsorbent in various forms: for example, columns of powdered crystalline material can give good results, as can a pelletized form obtained by pressing a mixture of beta zeolite with a suitable binder, such as clay, into pellets.
[0046] Highly active conversion catalysts can be obtained by treating the beta zeolites of this invention with a fluid medium containing sufficient hydrogen ions or ions convertible to hydrogen ions to impart catalytic properties. The catalysts thus obtained have a broad spectrum of catalytic activity and can be used in very low concentrations, making it possible to carry out certain hydrocarbon conversion processes at practical and controllable rates at temperatures much lower than those previously employed.
[0047] A contemplated high activity catalyst is obtained by contacting the beta zeolite of the present invention with a fluid medium containing hydrogen ions or ions convertible thereto, washing the treated product free of soluble anions, then drying and heating the product at a temperature ranging from about 400°F (204°C) to 1700°F (927°C) or higher for a period of about 1 to 48 hours to thermally activate the product. The resulting product is an activated aluminosilicate, is highly acidic, contains less than about 10% by weight metals, and substantially corresponds to the hydrogen form of the beta zeolite precursor material. The resulting product has then been found to be active as a catalyst for hydrocarbon conversion when used alone or dispersed or otherwise intimately admixed in a particle size of less than about 40 microns.
[0048] Compositions obtained by treating beta zeolite with a fluid medium containing hydrogen ions, ammonium ions, or complex ammonium and metal ions, or mixtures thereof, can be used as catalysts in a wide variety of hydrocarbon conversion processes, including isomerization / hydroisomerization, disproportionation, olefin hydration, olefin amination, oxidation, dehydrogenation, alcohol dehydration, desulfurization, hydrogenation, reforming, hydrocracking, polymerization, and the like. These catalysts are stable at temperatures ranging from 70°F (21°C) to 1000°F (538°C), including periodic regeneration of the catalyst by burning off combustible deposits. Due to their high catalytic activity, the catalysts are useful for carrying out a variety of hydrocarbon conversion processes, such as alkylation, at relatively low temperatures with small amounts of catalyst, thereby minimizing undesirable side reactions and operating costs.
[0049] The catalyst comprising the heteroatom-doped beta zeolite of the present invention can be used as such or as an intermediate in the preparation of further reforming contact masses comprising low activity or catalytically active materials that act as supports or matrices for the aluminosilicates. The catalyst can be used in powder, granular or shaped form, formed into spheres or pellets of finely divided particles having a particle size of 2 to 500 mesh. If the catalyst is shaped, such as by extrusion, the aluminosilicate can be extruded before drying or can be extruded after drying or partial drying. The catalyst product is preferably pre-decarboxylated in an inert atmosphere or undergoes initial decarboxylation during use in the conversion process. Generally, the composition is dried between 150°F (66°C) and 600°F (315°C) and then calcined in air or steam, or in an inert atmosphere such as nitrogen, hydrogen, helium, or exhaust gas, at a temperature ranging from 400°F (204°C) to 1700°F (927°C) for a period of time ranging from 1 hour to 48 hours or more. This heating step is known as thermal activation of the catalyst.
[0050] The catalyst of the present invention can be prepared in any desired physical form, including pieces of a size optimal for operation under the particular conditions present. Thus, the catalyst can be in the form of a finely divided powder or, for example, in the form of pellets of 1 / 16" to 1 / 8" size obtained by pelletizing, casting, extruding according to well-known techniques.
[0051] The catalyst of the present invention is useful in hydroisomerization processes that include catalysts with low silica to alumina ratios.For example, the silica to alumina ratio in the zeolite can be less than about 200:1, such as less than about 110:1, or less than about 100:1, or less than about 90:1, or less than about 75:1.In various embodiments, the silica to alumina ratio can be 50:1 to 200:1, such as 20:1 to 160:1, or 30:1 to 100:1.
[0052] In an embodiment, the catalyst of the present invention includes a metal hydrogenation component. The metal hydrogenation component is typically a Group VIB and / or Group VIII metal. In one embodiment, the metal hydrogenation component can be Pt, Pd, or a mixture thereof. In another embodiment, the metal hydrogenation component can be a combination of a non-noble Group VIII metal and a Group VIB metal.
[0053] The metal hydrogenation component is added to the catalyst in any convenient manner. One technique for adding the metal hydrogenation component is by incipient wetness. For example, the zeolite and binder can be combined and then the combined zeolite and binder can be extruded into catalyst particles. The catalyst particles are exposed to a solution containing the appropriate metal precursor. Alternatively, the metal can be added to the catalyst by ion exchange, where the metal precursor is added to the zeolite (or zeolite and binder) mixture prior to extrusion.
[0054] The amount of metal in the catalyst can be at least 0.1 wt.%, or at least about 0.15 wt.%, or at least about 0.2 wt.%, or at least about 0.25 wt.%, or at least about 0.3 wt.%, or at least about 0.5 wt.% based on the catalyst. The amount of metal in the catalyst can be about 20 wt.% or less, or about 10 wt.% or less, or about 5 wt.% or less, or about 2.5 wt.% or less, or about 1 wt.% or less based on the catalyst. When the metal is Pt, Pd, other Group VIII noble metals, or combinations thereof, the amount of metal can be about 0.1 to about 5 wt.%, about 0.1 to about 2 wt.%, or about 0.25 to about 1.8 wt.%, or about 0.4 to about 1.5 wt.%. In embodiments where the metal is a combination of non-noble Group VIII and Group VIB metals, the combined amount of the metals may be from 0.5 wt.% to 20 wt.%, or from 1 wt.% to 15 wt.%, or from 2.5 wt.% to 10 wt.%.
[0055] The catalyst of the present invention may also include a binder. In some embodiments, the degreased catalyst may be formulated with a low surface area binder, where the low surface area binder has a surface area of less than 100 m 2 / g or less, or 80m 2 / g or less, or 70m 2 The binder represents a binder having a surface area of 0.1 wt. / g or less. The amount of zeolite in a catalyst formulated with the binder can be from about 30 wt.% zeolite to 90 wt.% zeolite based on the combined weight of the binder and zeolite. The amount of zeolite is at least about 50 wt.%, for example at least about 60 wt.% or from about 65 wt.% to about 80 wt.%, based on the combined weight of the zeolite and binder.
[0056] In accordance with various embodiments of the present invention, the zeolite can be combined with the binder in any convenient manner. For example, the bound catalyst can be produced by starting with powders of both the zeolite and the binder, adding water to the powders to form a mixture, and then extruding the mixture to produce the bound catalyst of the desired size. Extrusion aids can also be used to modify the extrusion flow characteristics of the zeolite and binder mixture. The amount of framework alumina in the catalyst ranges from 0.1 to 3.33 wt.%, or 0.1 to 2.7 wt.%, or 0.2 to 2 wt.%, or 0.3 to 1 wt.%.
[0057] Hydroisomerization Process Hydroisomerization of linear and monobranched paraffins (alkanes) can improve the octane number of gasoline fuel products. Paraffin isomerization using bifunctional catalysts, such as zeolites or mixed metal oxide catalysts, promotes paraffin isomerization by dehydrogenation, protonation to form carbenium ions, and skeletal rearrangement of the carbenium ions via mechanisms such as those involving cyclopropyl cations.
[0058] In a conventional paraffin hydroisomerization process, a hydrocarbon feed is heated in the presence of hydrogen and a suitable bifunctional catalyst. For example, U.S. Patent Application Publication No. 2013 / 0324782 describes one conventional paraffin isomerization process in which a bifunctional catalyst is used. Furthermore, U.S. Patent Nos. 6,080,904 and 6,124,232 provide details of the bifunctional catalyst, which is an acidic metal oxide catalyst, and the C 5 and C 6 Paraffin isomerization processes in which straight-chain (normal) paraffins undergo isomerization using such catalysts. Other catalysts, including chlorinated alumina, sulfated zirconia, and certain zeolites, are highly selective for cracking and produce C 5 and C 6 Normal paraffins can be isomerized.
[0059] In contrast, C 7+ Normal paraffins are prone to cracking under isomerization conditions, especially at high reaction temperatures. Excessive cracking leads to lower yields of the desired branched paraffins and a lower octane number. Without being bound by theory or mechanism, it is believed that cracking occurs via β-scission of cationic intermediates. During β-scission, C 5 , C 6 Normal paraffins form primary carbenium ions called ethyl cations, but this is difficult. 7+ Paraffins may form more stable and easier to produce secondary or tertiary carbenium ions upon β-fission. Therefore, under isomerization reaction conditions, the favorable thermodynamics for promoting cracking are such that C 7+ Paraffin cracking can be difficult to suppress.
[0060] U.S. shale oil production is growing rapidly. Shale oil typically requires additional processing for use in blended fuels. High octane branched hydrocarbons are desirable as blending components for premium gasoline production, but C 7 and C 8Straight-chain paraffins are the main component of this hydrocarbon resource, and are prone to cracking in conventional processing. 8+ While viable for some components, catalytic reforming is energy inefficient and leaves a significant portion of the hydrocarbon resource unconverted.
[0061] As mentioned above, hydroisomerization of normal paraffins increases the octane number, but 7+ Excessive cracking of normal paraffins is problematic in many ways. 7+ To counter the thermodynamic favorability of cracking normal paraffins, isomerization is carried out at lower temperatures and lower feed mixture conversions, which may be undesirable from a process efficiency standpoint. Therefore, the isomerization of hydrocarbon resources rich in normal paraffins, such as naphtha, especially C 7+ It is difficult to improve the octane number of hydrocarbon resources that contain a large amount of unbranched or monobranched paraffins.
[0062] As provided herein, hydroisomerization involves the use of equilibrium-determined C 7 and using a catalyst capable of selectively converting high carbon number light paraffins in the mixed feed to achieve a maximum conversion level of C. 5 and C 6 and carrying out further hydroisomerization on the unconverted light paraffins to obtain highly branched products. In this method, the hydrocarbon feed for hydroisomerization is 5 -C 30 Normal paraffin, e.g. C 5 -C 7 Normal paraffin, or C 7+ The hydrocarbon feedstock may include normal paraffins and / or mono-branched paraffins. 7+ Normal paraffin, C 8 -C 30 Normal paraffins, as well as monobranched paraffins (e.g., C 5 Monobranched paraffin, C6 Monobranched paraffin or C 7+ Monobranched paraffin), C 5 Normal paraffin, C 6 Thus, the hydrocarbon feedstock may further comprise normal or mono-branched C 5 Paraffin, normal or mono-branched C 6 Paraffin, and normal or mono-branched C 7 Paraffin. Optionally, at least some normal or mono-branched C 8 Paraffins are also present in such hydrocarbon feedstocks. Other hydrocarbon feedstocks useful in the catalyst of the present invention include C 10 -C 10 Any of the aforementioned hydrocarbon feedstocks may further comprise one or more aromatic compounds.
[0063] Optionally, one or more naphthenic compounds are used in combination with the hydrocarbon feedstock. The incidence of cracking can be further reduced by including one or more naphthenic compounds as a co-feed. There can be about 10 wt.% or more naphthenic compounds in combination with the hydrocarbon feedstock. Suitable naphthenic compounds include branched naphthenic compounds such as methylcyclopentane (MCP), methylcyclohexane (MCH), or combinations thereof. Other suitable branched naphthenic compounds such as ethylcyclopentane, propylcyclopentane, 1,1-dimethylcyclopentane, 1,1-dimethylcyclohexane, ethylcyclohexane, propylcyclohexane, and the like are also suitable for use in the processes described herein, including bicyclic naphthenic compounds. In general, any naphthenic compound capable of forming a tertiary carbenium ion under isomerization reaction conditions can be effectively used with the catalyst of the present invention in the hydroisomerization process.
[0064] In the hydroisomerization process, one or more catalysts are contacted with a hydrocarbon feed under one or more of the following isomerization reaction conditions: a temperature ranging from about 150° C. to about 300° C., or from about 170° C. to about 270° C.; a molar ratio of hydrogen to hydrocarbon feed ranging from about 1:1 to about 3:1; a pressure ranging from about 100 psig to about 350 psig; and a liquid hourly space velocity of about 0.5 h -1 About 6 hours from -1 The hydrogen partial pressure can range, for example, from about 50 kPa to about 2000 kPa. In a particular example, the hydroisomerization reaction conditions are for about 6 hours. -1 Less than or equal to 5 hours -1 Less than or equal to 4 hours -1 Below, and about 2 hours -1 About 5 hours from -1 The hydroisomerization reaction conditions are those conditions in which the hydroisomerization reaction is carried out in the gas phase, supercritical phase or liquid phase. The hydroisomerization reaction conditions include the liquid hourly space velocity of C 5 -C 7 The conversion of normal paraffins is about 95% or less, or about 90% or less, or about 85% or less, or about 80% or less, or about 75% or less, or about 70% or less. 7+ The conversion rate of normal paraffins is about 70% to about 90%. The cracking yield of n-heptane is about 10 wt.% or less, and the ratio of n-heptane isomerization yield:cracking yield is about 10 or more, for example, about 10 to about 25, or about 10 to about 20.
[0065] Pt / Fe / WZrO x catalyst As taught in co-pending U.S. Provisional Application 17 / 349986 (2021EM062-US), Pt / Fe / WZrO x The mixed metal oxide catalyst, referred to as catalyst (or EMM-62), is at least partially crystalline and includes tungsten, zirconium, and a variable oxidation state metal. The variable oxidation state metal includes a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof. Pt / Fe / WZrO xThe catalyst has about 5 wt% to about 25 wt% tungsten, about 40 wt% to about 70 wt% zirconium, and about 0.01 wt% to about 5 wt% of the variable oxidation state metals, based on the total weight of the mixed metal oxide. x The catalyst is approximately 50m 2 / g or more and at least one of an ammonia uptake of about 0.05 mmol / g to about 0.3 mmol / g as measured by temperature programmed adsorption / desorption method, or a collidine uptake of about 100 μmol / g or more as measured by gravimetry.
[0066] Pt / Fe / WZrO x To produce the catalyst, zirconium, tungsten, and a variable oxidation state metal are combined in a reaction mixture under alkaline conditions having a pH of about 7.5 or greater. The variable oxidation state metal comprises a metal selected from the group consisting of Fe, Mn, Co, Cu, Ce, Ni, and any combination thereof. Under alkaline conditions, a slurry is obtained that includes a co-precipitation reaction product formed from zirconium, tungsten, and the variable oxidation state metal. The slurry is digested to form an amorphous digestion product from the co-precipitation reaction product. The amorphous digestion product is calcined in air at a temperature in the range of about 700° C. to about 900° C. to obtain a mixed metal oxide that is at least partially crystalline and includes about 5 wt.% to about 25 wt.% tungsten, about 40 wt.% to about 70 wt.% zirconium, and about 0.01 wt.% to about 5 wt.% variable oxidation state metal, respectively, based on the total weight of the mixed metal oxide. This mixed metal oxide has a total surface area of approximately 50 m, measured according to ISO 9277. 2 / g or more, and has at least one of an ammonia uptake of about 0.05 mmol / g to about 0.3 mmol / g as measured by a temperature programmed adsorption / desorption method, or a collidine uptake of about 100 μmol / g or more as measured by a gravimetric method.
[0067] Pt / Al-MOR catalyst As described in published international patent applications WO2016 / 126431 and WO2018 / 160327, the Pt / Al-MOR catalyst is 2 / g and containing aggregates composed of primary crystallites having an average primary crystallite size of less than 80 nm as measured by TEM, an aspect ratio of less than 2, and a total surface area of 500 m 2 In some embodiments, the Pt / Al-MOR catalyst (sometimes referred to as EMM-34) has a mesopore surface area to total surface area ratio of 0.05 or greater and is synthesized from TEA or MTEA.
[0068] The Pt / Al-MOR catalyst, also called meso-mordenite, is synthesized from the structure directing agent TEA (tetraethylammonium cation) or MTEA (methyltriethylammonium cation) and is dissolved in 30 ml of water. 2 / g and containing aggregates composed of primary crystals, the primary crystals having an average primary crystal size of less than 80 nm and an aspect ratio of less than 2 as measured by TEM.
[0069] The Pt / Al-MOR catalyst has a mesopore surface area of 30 m2 measured by the BET method. 2 / g or more, 40m 2 / g or more, in some cases 45m 2 / g or more. The Pt / Al-MOR catalyst comprises aggregates, typically irregular aggregates, made up of primary crystallites having an average primary crystallite size of less than 80 nm, less than 70 nm, less than 60 nm, e.g., less than 50 nm, as measured by TEM. The primary grains may have an average primary crystallite size of 20 nm or more, optionally in the range of 30 nm to less than 80 nm, as measured by TEM.
[0070] Optionally, the primary crystallites of the Pt / Al-MOR catalyst have an average primary crystallite size of less than 80 nm, less than 70 nm, and in some cases less than 60 nm in each of the a, b, and c crystal vectors as measured by X-ray diffraction. The primary crystallites can optionally have an average primary crystallite size in the range of greater than 20 nm, optionally greater than 30 nm to less than 80 nm in each of the a, b, and c crystal vectors as measured by X-ray diffraction.
[0071] Pt / Al-MOR catalysts are generally composed of a mixture of primary crystal aggregates along with non-agglomerated primary crystals. The majority of the Pt / Al-MOR catalyst, e.g., between 80 wt% and 90 wt%, exists as primary crystal aggregates. The aggregates are generally irregularly shaped. For details on aggregates, see, for example, Walter, D., Primary Particles-Agglomerates-Aggregates, in Nanomaterials, Deutsche Forschungsgemeinschaft (DFG), Wiley, 1-24, 2013.
[0072] Optionally, the Pt / Al-MOR catalyst comprises at least 50% by weight, at least 70% by weight, advantageously at least 80% by weight, and at least 90% by weight, and optionally consists essentially of irregular aggregates composed of primary crystallites having a primary crystal size of less than 80 nm, less than 70 nm, and less than 60 nm, for example less than 50 nm. The Pt / Al-MOR catalyst has less than 10% by weight of primary crystallites having a size greater than 80 nm as assessed by TEM. The Pt / Al-MOR catalyst has irregular aggregates composed of crystallites having a crystal size of less than 80 nm as measured by TEM. The Pt / Al-MOR catalyst is substantially free of needle-shaped or plate-shaped crystals (e.g., contains less than 10% of the number of needle-shaped or plate-shaped crystals as assessed by TEM).
[0073] The primary crystallites of the Pt / Al-MOR catalyst have an aspect ratio of less than 3.0, more preferably less than 2.0, where the aspect ratio is defined as the longest dimension of the crystallite divided by the width of the crystallite, where the width of the crystallite is defined as the dimension of the crystallite at the middle of its longest dimension in a direction perpendicular to its longest dimension, as measured by TEM.
[0074] The aggregates of primary crystallites are typically irregular in morphology and may be referred to as "secondary" particles because they are formed from aggregates of crystallites that are "primary" particles. The primary grains may have a narrow size distribution such that at least 90% of the primary grains by number have an average primary grain size in the range of 20-80 nm and / or 20-60 nm, as measured by TEM.
[0075] The Pt / Al-MOR catalyst was 500m 2 / g or more, 550m 2 / g or more, in some cases 600m 2 / g or more. The total surface area includes the surface area of the internal pores (zeolite surface area) and the surface area of the outside of the crystals (external surface area). The total surface area is measured by the BET method. The ratio of the mesopore surface area to the total surface area of the Pt / Al-MOR is 0.05 or more. The mesopore volume of the Pt / Al-MOR catalyst is 0.1 mL / g or more, and / or 0.12 mL / g or more, and in some cases 0.15 mL / g or more. EXAMPLES
[0076] Features of the methods and compositions of the invention are described in the following non-limiting examples.
[0077] Example 1: Synthesis of heteroatom-doped beta zeolite Zeolite synthesis Aluminum nitrate (Al(NO 3 ) 3 9H 2 O) and heteroatom nitrates (Ce(NO 3 ) 3 6H 2 O or Co(NO 3) 2 6H 2 The clear solution was dissolved in deionized water to form a clear solution. 2 A tetraethylammonium hydroxide (TEAOH) solution (35 wt.%) was added and mixed to obtain a homogeneous gel. The homogeneous gel was placed in a Teflon-lined steel autoclave and heated under hydrothermal conditions at 150 °C with 20 rpm rotation for approximately 5-6 days. The molar ratios were as follows: SiO 2 :TEAOH:Al(NO 3 ) 3 :M(NO 3 ) x :H 2 O is equal to 1:0.4:0.05:y:16, typically y is 0.005 or 0.01, or y is 0 to obtain Al-Beta zeolite, which is used as a control catalyst.
[0078] The zeolite was collected by centrifugation (usually 12000 rpm, 5 min, repeated 3 times) and dried in an oven at 120 °C overnight. Calcination was performed at 550 °C for 6 h with a 3 h heat-up period. Finally, Pt(NH 3 ) 4 (NO 3 ) 2 Ion exchange with 10 grams of solution / 1 gram of zeolite was carried out for 24 hours to give 0.6 wt.% Pt in the final product. The zeolite was collected by centrifuge and calcined at 550°C for 3 hours.
[0079] Characterization The X-ray diffraction pattern ("XRD") of Ce-doped Al-beta zeolite (also referred to herein as "Ce,Al-beta") with Si / Ce=100 is shown in the top row of FIG. 1 and compared with Al-beta zeolite (also referred to herein as "Al-beta") in the bottom row of FIG. 1. *A BEA-type zeolite framework (also referred to herein as BEA, or beta-type zeolite, or beta-structure-type zeolite) was obtained under these crystallization conditions and in the presence of cerium ("Ce") in the synthesis gel. DRUV-vis results of the Ce-loaded zeolite before and after calcination are shown in Figure 2. Ce,Al-Beta before calcination is shown in the first row. Ce,Al-Beta after calcination is shown in the second row. Reference CeO 2 The absorption intensities based on the Kubelka-Munk function of are reduced to 1 / 20 of the original values for ease of comparison. Figure 2, line 3.
[0080] DRUV-vis spectra detect the state of the heteroatoms through the ligand-to-metal charge transfer or "LMCT" bands. In the case of monoatomic heteroatoms, this corresponds to a charge transfer from oxygen to the metal. In the case of oligomers or bulk oxides, this charge transfer corresponds to an electron transfer from the HOMO to the LUMO electronic band. Thus, the absorption peak corresponding to the energy of the absorbed phonon indicates the degree of isolation (or oligomerization) of the heteroatom oxide. In many cases, this is a qualitative indicator of the state of the heteroatoms. As shown, the state of Ce changes before and after the calcination process, and the degree of isolation is reduced by this treatment. This result indicates the formation of oligomeric cerium oxide at extra framework sites in the calcined zeolite. In bulk CeO 2 Compared to the reference spectrum, the absorption edge is shifted to shorter wavelengths, indicating a degree of oligomerization that does not form a bulk structure.
[0081] These characterization results indicate that the obtained product is beta zeolite and CeO x This indicates that the nanoclusters are a complex of nanoclusters of the same species, which are likely in close proximity to the framework as they retain a high degree of dispersion.
[0082] Example 2: C using zeolite powder 7 Hydroisomerization Reaction The calcined zeolite powder was sieved through a No. 40 / 60 sieve. The reaction was carried out in a high throughput fixed bed reactor with the following activation procedure:
[0083] Temperature is N 2 (100 standard cubic centimeters per minute ("sccm")) to 250°C (ramp rate of 60°C / hr) and held at 250°C for 1 hour. The temperature was then reduced to 220°C (ramp rate of 60°C / hr) and the reactor flow was reduced to H 2 The back pressure was changed to 200 pounds per square inch gauge ("psig"). 2 The reduction was carried out for 3 hours (100 sccm). The reactor temperature was then set to the desired reaction temperature. The hydrocarbon feed stream was H 2 :nC 7 Set the molar ratio to 2:1 and H 2 and C 7 The partial pressures of were 137.1 pounds per square inch absolute ("psia") and 70.4 psia, respectively.
[0084] As shown in Figure 3, the Ce and Co doped zeolites showed better conversion-selectivity trade-off curves for isomerization products compared to the undoped zeolites. The square symbols in Figure 3 represent the Pt / Ce,Al-Beta (WHSV = 2, 4, 6 h -1 Similarly, triangles represent Pt / Al-beta and circles represent Pt / Co,Al-beta, with WHSV=2, 4, and 6h, respectively. -1 , at 250 °C. For example, a selectivity increase of +5% was observed at a conversion of about 74%. The conversion-selectivity tradeoff of platinum doped Al-Beta zeolite (or "Pt / Al-Beta") far exceeds previous results seen in the literature (e.g. Wang 1997).
[0085] Interestingly, the incorporation of Sn into the framework lost selectivity towards isomerization products, with cracking becoming the predominant reaction pathway. Figure 4. Previously, it was shown that the introduction of zirconium (Zr) significantly increased the reaction temperature to achieve comparable conversions. See, for example, US Patent Application Publication No. 2015 / 0273450. Here, the maximum yield also decreased, making this material inferior compared to its other counterparts. Thus, the correct selection of dopant elements is crucial to improve performance. As shown in Figure 4, squares represent Pt / Ce,Al-beta, circles represent Pt / Co,Al-beta, and diamonds represent Pt / Sn,Al-beta at WHSV=2, 4, and 6 h, respectively. -1 The triangles represent the results of using Pt / Al-Beta at WHSV=4,6h. -1 , and the results are shown for 230°C.
[0086] FIG. 3 shows the isomerization selectivity (%) versus n-heptane conversion (%) for heteroatom-doped zeolites: (1) Pt / Al-Beta with 0.6 wt.% Pt and Si / Al of 20; (2) Pt / Ce,Al-Beta with 0.6 wt.% Pt, Si / Al of 20, and Si / Ce of 100; and (3) Pt / Co,Al-Beta with 0.6 wt.% Pt, Si / Al of 20, and Si / Co of 200, with WHSV of 2, 4, and 6 at 230° C., respectively. FIG. 4 shows the isomerization selectivity (%) versus n-heptane conversion (%) for heteroatom-doped zeolites: (1) Pt / Al-Beta with 0.6 wt.% Pt and Si / Al of 20; (2) Pt / Ce,Al-Beta with 0.6 wt.% Pt and Si / Al of 20; (3) Pt / Co,Al-Beta with 0.6 wt.% Pt, Si / Al of 20, and Si / Co of 200; (4) Pt / Sn,Al-Beta with 0.6 wt.% Pt, Si / Al of 20, and Si / Sn of 100 (SnCl25H 2 O), with WHSV of 2, 4, and 6 at 230 °C, respectively.
[0087] This example confirms that heteroatom-doped zeolites are useful as highly bifunctional catalysts to improve the conversion-selectivity tradeoff in hydroisomerization reactions.
[0088] Example 3: C as a light paraffin model 5 , C 6 , C 7 Hydroisomerization reaction using mixtures The calcined zeolite powder was sieved through a No. 40 / 60 sieve. The reaction was carried out in a high throughput fixed bed reactor with the following activation procedure: 2 (100 sccm) and the temperature was increased to 300° C. (60° C. / hour (hr) ramp rate) and held at 300° C. for 1 hour. The temperature was reduced to 220° C. (60° C. / hr ramp rate) and the reactor flow was reduced to H 2 with a back pressure of 350 psig. 2 Zeolite was changed to H 2 (100 sccm) for 24 hours. The reactor temperature was then set to the temperature specified for the reaction run. The hydrocarbon feed flow was as follows: 5 :nC 6 :nC 7 =1:1:1(weight ratio);H 2 :n-paraffin molar ratio=2:1 (molar ratio). The total pressure of the reactor was set at 180 psia.
[0089] FIG. 5A shows the thermal expansion of light gas (C 1 ~C 4 The results show the increase in research octane number ("RON") for the production of 1,000 sulphuric acid (1,000 sulphuric acid), which was carried out at weight time specific velocity ("WHSV") equal to 3 and 6 per hour. In Figure 5A, squares represent Pt / Ce,Al-beta, diamonds represent Pt / Al-beta, hexagons represent Pt / Al-MOR, and circles represent Pt / Fe / WZrO. x , WHSV=3,6h respectively -1 FIG. 5B shows the conversion rate of n-heptane (wt.%) versus C 1 ~C 4 In Fig. 5B, the squares represent Pt / Ce,Al-beta, the diamonds represent Pt / Al-beta, the hexagons represent Pt / Al-MOR, and the circles represent Pt / Fe / WZrO. x , WHSV=3,6h respectively -1 It is expressed as:
[0090] As shown in these Figures 5A and 5B, the Ce-doped Al-Beta zeolite showed step-out performance to selectively isomerize the feed to increase the RON under limited cracking. For example, Pt / Ce,Al-Beta enhanced the RON by +18 while producing only about 1 wt.% light gas cracking products, which is higher than the Pt / Fe / WZrO mixed metal oxide catalyst used for this type of reaction. x The reaction temperature is equal to or slightly better than that of Pt / Fe / WZrO x (EMM-62) at 250°C and Al-Beta zeolite (EMM-62) at 170°C, with the Al-Beta zeolite sample produced by the method of the present invention operating at the more severe conditions which favor cracking. Catalysts based on mixed metal oxides are capable of operating at lower temperatures and therefore have performance advantages when used for this purpose. However, in this example, the Al-Beta zeolite was shown to perform as well as the modified mixed metal oxide catalysts.
[0091] The contrast of Plysine with Pt / Al-Beta zeolite is evident from the slope of RON enhancement per total light gas produced. This result supports Ce acting as a selectivity promoter. Pt / Al,MOR is a current zeolite used in light paraffin isomerization and was used as a model reference for comparison. This zeolite used is described in PCT Publication No. WO2018 / 160327, paragraphs
[0053] ,
[0055] ,
[0058] ,
[0059] -
[0064] , which are incorporated herein by reference. Platinum Al-MOR (Pt / Al-MOR) has higher cracking selectivity compared to Pt / Ce,Al-Beta zeolite, likely due to the stronger acidity of the zeolite. These comparative results reinforce the practical advantages of Pt / Ce,Al-Beta zeolite over other zeolite-based hydroisomerization catalysts.
[0092] Also, C in the feed mixture 7At the conversion level of 10 ... 7 See results using feed. In general, there is another notable advantage that improves the performance of hydroisomerization processes. Most of the conventional zeolite-based paraffin isomerization units use C 5 , C 6 However, depending on the concentration level in the hydrocarbon feedstock, 7 The process of the present invention has the advantage that existing isomerization capacity can be utilized for the entire process without an upstream purification step, thus reducing the capital investment required to install new reactors.
[0093] As shown in Fig. 6, the squares represent Pt / Ce,Al-beta, the diamonds represent Pt / Al-beta, the hexagons represent Pt / Al-MOR, and the circles represent Pt / Fe / WZrO. x , respectively LHSV=3,6h -1 Pt / Ce,Al-beta, Pt / Al-beta, Pt / Fe / WZrO x C 7 Against C 6 The relative conversions of Pt / Ce,Al-beta zeolite and C 7 , C using Pt / Ce,Al-beta zeolite 6 The same trend was observed for C 5 (not shown). This result indicates the difference in the nature of the active sites and thus the influence of heteroatom doping on the zeolite.
[0094] C 7 The preferential conversion of the light paraffin feed (C 5 -C 7 ) but C 7Partially converted C which can be first converted to achieve a maximum conversion level (determined by equilibrium) and then further processed using existing light paraffin hydroisomerization units. 5 and C 6 This is useful when designing a process that is followed by a separation unit to remove C. 5 , C 6 It is designed to selectively convert C in the hydrocarbon feedstock. 7 Concentration levels are limited, but as noted above, existing isomerization capacity can be utilized for overall conversion, reducing the capital investment required to install new reactors.
[0095] Example 4: C using zeolite extrudates with alumina binder 7 Hydroisomerization Reaction The reaction was carried out in a high throughput fixed bed reactor using 70 / 30 zeolite / alumina extrudates, showing that the extrudates were also active for this reaction.
[0096] The reaction conditions are as follows: 2 The supported catalyst was preconditioned by heating the reactor from 100°C to 400°C while flowing hydrogen at a rate of 200 cubic centimeters per hour for 6 hours. Chemical grade n-heptane feed was introduced in a continuous flow manner using two alternating 100 cubic centimeter ("cc") ISCO pumps. The feed was delivered to the reactor through a heated line and the hydrogen flow rate was set using a Brooks mass flow controller. The pressure was maintained at 350 psig. The feed was then pumped through the catalyst bed, which was held at a reaction temperature of 230°C, with different LHSVs, a hydrogen:hydrocarbon molar ratio of 2:1, and a pressure of 350 psig. The liquid products exiting the reactor flowed through heated lines and were analyzed using a gas chromatograph with an FID detector.
[0097] Compared to the results of Example 2, the Co loading of Co,Al-Beta zeolites was increased from Si / Co=200 to Si / Co=100. These new zeolites yielded conversion trade-off curves similar to their Ce counterparts. In Figure 7, the square symbols represent Pt / Ce,Al-Beta (LHSV=0.75, 1, 1.5h -1 ), and the circles represent the conversion by Pt / Co,Al-beta (LHSV=0.75, 1, 1.5h -1 ) This result indicates that the heteroatom loading also plays an important role in the catalytic performance as a promoter, and the extruded zeolite remains active for this reaction.
[0098] Numerous changes, modifications, and variations will be apparent to those of skill in the art in light of the foregoing description without departing from the spirit or scope of the present disclosure, and where numerical lower limits and numerical upper limits are listed herein, ranges from any lower limit to any upper limit are contemplated.
[0099] Additionally or alternatively, the present invention relates to:
[0100] Embodiment 1: A process for hydroisomerizing a hydrocarbon feedstock comprising contacting the hydrocarbon feedstock with hydrogen and a catalyst to obtain a hydrocarbon product having an increase in branched hydrocarbons relative to the hydrocarbon feedstock, the catalyst comprising a heteroatom-doped beta zeolite having an exo-framework species comprising trivalent cations, cerium and / or cobalt as framework metal oxides, and 0.01-1.5 wt % of a Group VIII or Group VIB metal, or a combination thereof.
[0101] Embodiment 2: Heteroatom-doped beta zeolite has a SiO ratio of greater than 10 framework / extraframework metal oxides. 2 2. The method of embodiment 1, comprising the molar ratio of:
[0102] Embodiment 3: The heteroatom-doped beta zeolite has an Al content greater than 8. 2 O 3 SiO 23. The method of embodiment 1 or 2, comprising a molar ratio of:
[0103] Embodiment 4: The heteroatom-doped beta zeolite is a zeolite having greater than 10 cerium and / or cobalt metal oxides (CeO x and CoO x (expressed as 2 The method of any one of the preceding embodiments, comprising a molar ratio of:
[0104] Embodiment 5: The method of any one of the preceding embodiments, wherein the catalyst further comprises a metal oxide binder.
[0105] Embodiment 6: The method of any one of the previous embodiments, wherein the group VIII or VIB metal is Pt, in particular, the catalyst comprises 0.1 wt.% to 1.5 wt.% Pt.
[0106] Embodiment 7: The method of any one of the preceding embodiments, wherein the hydrocarbon feedstock is contacted with the catalyst under one or more isomerization conditions.
[0107]
[0023] Embodiment 8: The one or more isomerization conditions include a temperature of 100°C to 450°C, a pressure of 0 psig to 1000 psig, and a reaction temperature of 0.1 hr. -1 ~10hr -1 and / or a hydrogen / hydrocarbon molar ratio of about 0.1 to about 100.
[0108] Embodiment 9: The method of any one of the previous embodiments, wherein the heteroatom-doped beta zeolite is selective for n-heptane conversion.
[0109] Embodiment 10: The method of any one of the previous embodiments, wherein the hydrocarbon feedstock comprises n-pentane, n-hexane, and / or n-heptane.
[0110]
[0031] Embodiment 11: The method of embodiment 10, wherein the hydrocarbon feedstock further comprises naphthenes and / or one or more aromatic compounds.
[0111]
[0036] Embodiment 12: Heteroatom-doped beta zeolite converts light paraffins in a hydrocarbon feedstock to C 5 ,C 6 and C 7 4. The method of any one of the preceding embodiments, wherein the
[0112] Embodiment 13: C 5 and C 6 C 7 13. The method of embodiment 12, wherein the method is separated from
[0113] Embodiment 14. A method for synthesizing a heteroatom-doped beta zeolite containing cerium or cobalt as an extra-framework species, comprising crystallizing a reaction mixture suitable for the synthesis of beta zeolite, in particular aluminum-containing beta zeolite (Al-beta zeolite), wherein at least one of cerium and cobalt is added to the reaction mixture prior to crystallization, preferably as a cerium and / or cobalt salt, in particular as a cerium and / or cobalt nitrate, sulfate, acetate, and / or halide.
[0114] Embodiment 15: The reaction mixture comprises water, SiO 2 and a framework metal oxide, the reaction mixture comprising: SiO of the reaction mixture 2 the molar ratio of the structure directing cation Q to SiO to framework metal oxide of the reaction mixture greater than 10 2 Molar ratio of; The SiO of the reaction mixture is greater than 0. 2 Molar ratio of water to; SiO of the reaction mixture from 0 to 1 2 the molar ratio of alkali metal M to SiO relative to the Al source of the reaction mixture greater than 5 2 15. The method of embodiment 14, comprising the molar ratio of:
[0115]
[0043] Embodiment 16: The reaction mixture comprises at least one source of cerium and / or cobalt greater than 10 (CeOx and CoO x (expressed as 2 16. The method of embodiment 14 or 15, comprising a molar ratio.
[0116] Embodiment 17: The method according to any one of embodiments 14 to 16, wherein the reaction mixture further comprises a structure directing agent and / or a mineralizer, preferably the reaction mixture comprises tetraethylammonium (TEA) ions as a structure directing agent.
[0117] Embodiment 18: The method of any one of embodiments 14 to 17, further comprising calcining the heteroatom-doped beta zeolite under inert, oxidative and / or steam conditions at a temperature between about 100° C. and about 800° C.
[0118] Embodiment 19. The chemical composition of the reaction mixture (in the absence of a cerium source and / or a cobalt source) is 2 O, Al 2 O 3 , [(C 2 H 5 )N] 2 O(TEAOH), SiO 2 , and H 2 The method according to any one of embodiments 14 to 18, wherein the composition of the reaction mixture is expressed as a mixture of SiO, SiO, and O; preferably, the composition of the reaction mixture is expressed in molar ratios. 2 / AlO 2 is about 10 to about 200, Na 2 O / TEAOH is about 0.0 to about 0.1, TEAOH / SiO 2 , about 0.1~about 1.0, H 2 O / TEAOH is about 20 to about 75.
[0119] Embodiment 20: The method of any one of embodiments 14-19, wherein the reaction mixture is heated at a temperature of about 75° C. to about 200° C. until crystallization occurs.
[0120] Embodiment 21: A composition comprising a beta zeolite having extraframework species of cerium and / or cobalt and about 0.01 to about 1.5 wt. % platinum.
[0121] Embodiment 22: Beta zeolite is a SiO to framework metal oxide of greater than 10 2 22. The composition of embodiment 21, comprising a molar ratio of:
[0122] Embodiment 23: Beta zeolite has an Al content greater than 8 2 O 3 SiO 2 23. The composition of embodiment 21 or 22, comprising a molar ratio of:
[0123] Embodiment 24: Beta zeolite is a zeolite having a cerium and / or cobalt metal oxide (CeO x and CoO x (expressed as 2 24. The composition of any one of embodiments 21-23, comprising a molar ratio of:
Claims
1. 1. A process for hydroisomerizing a hydrocarbon feed comprising contacting the hydrocarbon feed with hydrogen and a catalyst to obtain a hydrocarbon product having an increase in branched hydrocarbons compared to the hydrocarbon feed, the catalyst comprising a heteroatom-doped beta zeolite having an extraframework species comprising trivalent cations, cerium and / or cobalt as framework metal oxides, and 0.01 to 1.5 wt % of a Group VIII or Group VIB metal, or a combination thereof.
2. The heteroatom-doped beta zeolite has a SiO ratio of greater than 10 framework / extraframework metal oxides. 2 The method of claim 1 comprising the molar ratio of:
3. The heteroatom doped beta zeolite has an Al content greater than 8. 2 O 3 SiO 2 The method according to claim 1 or 2, comprising a molar ratio of:
4. The heteroatom-doped beta zeolite has more than 10 cerium and / or cobalt metal oxides (CeO x and CoO x (expressed as 2 The method according to claim 1 or 2, comprising a molar ratio of:
5. The method of claim 1 or 2, wherein the catalyst further comprises a metal oxide binder.
6. The method of claim 1 or 2, wherein the Group VIII or Group VIB metal is Pt, and preferably the catalyst comprises 0.1 wt.% to 1.5 wt.% Pt.
7. The hydrocarbon feedstock is contacted with the catalyst under one or more isomerization conditions, the one or more isomerization conditions being at a temperature between 100° C. and 450° C., at a pressure between 0 psig and 1000 psig, for 0.1 hr. ‐1 ~10hrs ‐1 and / or a hydrogen / hydrocarbon molar ratio of 0.1 to 100.
8. 3. The process of claim 1 or 2, wherein the heteroatom-doped beta zeolite is selective for n-heptane conversion.
9. The method of claim 1 or 2, wherein the hydrocarbon feedstock comprises n-pentane, n-hexane, and / or n-heptane.
10. 10. The method of claim 9, wherein the hydrocarbon feedstock further comprises naphthenes and / or one or more aromatic compounds.
11. The heteroatom-doped beta zeolite converts light paraffins in the hydrocarbon feedstock into C 5 , C 6 and C 7 The method according to claim 1 or 2, wherein the compound is selectively converted into
12. C 5 and C 6 C 7 The method of claim 11 , wherein the
13. A method for the synthesis of heteroatom-doped beta zeolite containing cerium or cobalt as an extra-framework species, comprising crystallizing a reaction mixture suitable for the synthesis of beta zeolite, in particular aluminum containing beta zeolite, and prior to crystallization, adding at least one of cerium and cobalt to the reaction mixture, preferably in the form of a cerium and / or cobalt salt, more preferably in the form of cerium and / or cobalt nitrates, halides, acetates and sulfates.
14. The reaction mixture comprises water, SiO 2 and a skeletal metal oxide, said reaction mixture comprising: 0 to 4 of the SiO 2 the molar ratio of the structure directing agent cation Q to SiO to framework metal oxide of the reaction mixture greater than 10 2 Molar ratio of SiO of the reaction mixture greater than 0 2 Molar ratio of water to 0 to 1 of the SiO 2 the molar ratio of alkali metal M to SiO relative to the Al source of the reaction mixture greater than 5 2 The method of claim 13 comprising a molar ratio of:
15. 15. The method according to claim 13 or 14, wherein the reaction mixture further comprises a structure directing agent and / or a mineralizer, preferably the reaction mixture comprises tetraethylammonium (TEA) ions as a structure directing agent.
16. 15. The method of claim 13 or 14, further comprising the step of calcining the heteroatom-doped beta zeolite at a temperature between 100°C and 800°C under inert, oxidative and / or steam conditions.
17. A composition comprising a beta zeolite having extra-framework species of cerium and / or cobalt and 0.01-1.5 wt % Pt.
18. Beta zeolite is a zeolite having a cerium and / or cobalt metal oxide (CeO x and CoO x (expressed as 2 The composition of claim 17 comprising a molar ratio.
19. Beta zeolite has an Al content greater than 8 2 O 3 SiO 2 19. The composition of claim 17 or 18, comprising a molar ratio of: